PENGARUH SISTEM TANAM JAJAR LEGOWO TERHADAP PRODUKTIVITAS DAN PENDAPATAN PETANI PADI SAWAH (ORYZA SATIVA L.) DI KOTA SUKABUMI (Suatu kasus pada petani padi sawah program LP2B) - Dikna Yalendra; Euis Dasipah; Dety Sukmawati (Universitas Galuh, 2022)
This study aims to analyze the differences in production costs, productivity, revenue and income used in lowland rice (Oriza lativa L.) farming with conventional planting systems and jajar legowo planting systems for farmers who participate in the LP2B program in Sukabumi City. The data analysis method used in this study is to use a statistical test t-test. The results showed that there were significant differences in the number of workers, namely the number of farm workers using the conventional planting system of 63.43 HOK/Ha and the farming using the jajar legowo planting system of 76.53 HOK/Ha; there is a difference in production costs, the conventional planting system is lower, namely Rp. 7,860,558,-/Ha, and the total cost of production in the jajar legowo planting system is higher, namely Rp. 8.810.753,-/Ha; there is a difference in productivity, which uses the conventional planting system, namely the productivity of 5,484 Kg/Ha; while the productivity with the jajar legowo planting system is 6,827 kg/ha; there is a significant difference in farm income, with a conventional planting system of Rp 23,580,930,-/Ha, with a row planting system of Rp 29,355,101/Ha. There is a significant difference in farm income with conventional cropping systems, which is Rp 15,720,372/Ha/MT, and the jajar legowo planting system of Rp 20,544,348/Ha/MT.